Breastfeeding is negatively affected by prenatal depression and reduces postpartum depression. - Figueiredo, Bárbara (2014)
Background. This prospective cohort study explored the effects of prenatal and postpartum depression on breastfeeding and the effect of breastfeeding on postpartum depression. Method. The Edinburgh Postpartum Depression Scale (EPDS) was administered to 145 women at the ﬁrst, second and third trimester, and at the neonatal period and 3 months postpartum. Self-report exclusive breastfeeding since birth was collected at birth and at 3, 6 and 12 months postpartum. Data analyses were performed using repeated-measures ANOVAs and logistic and multiple linear regressions. Results. Depression scores at the third trimester, but not at 3 months postpartum, were the best predictors of exclusive breastfeeding duration (β =−0.30, t=−2.08, p<0.05). A signiﬁcant decrease in depression scores was seen from childbirth to 3 months postpartum in women who maintained exclusive breastfeeding for53 months (F1,65 =3.73, p<0.10, ηp 2 =0.05). Conclusions. These ﬁndings suggest that screening for depression symptoms during pregnancy can help to identify women at risk for early cessation of exclusive breastfeeding, and that exclusive breastfeeding may help to reduce symptoms of depression from childbirth to 3 months postpartum.